Expression and cellular localization of hepcidin mRNA and protein in normal rat brain - Raha-Chowdhury, Ruma; Raha, Animesh Alexander; Forostyak, Serhiy; Zhao, Jing-Wei; Stott, Simon Russell William; Bomford, Adrian (BMC neuroscience, 2015)
BACKGROUND: Hepcidin is a peptide hormone belonging to the defensin family of cationic antimicrobial molecules that has an essential role in systemic iron homeostasis. The peptide is synthesised by hepatocytes and transported in the circulation to target tissues where it regulates the iron export function of the ferrous iron permease, ferroportin. In the brain hepcidin protein has been identified using immuno-histochemistry and mRNA by real-time PCR but not by in situ hybridisation raising the question of whether there is measurable transcription of the hepcidin gene in the central nervous system. Alternatively hepcidin could be transported as a hormone to the brain via the circulation. RESULTS: By RT-PCR hepcidin mRNA was present at low level throughout normal rat brain while in situ hybridisation to detect low-abundant mRNA revealed that transcripts were restricted to endothelium of blood vessels and choroid plexus. In contrast, hepcidin protein analysed by immuno-histochemistry was highly expressed in blood vessels, in endothelium and in pericytes. Hepcidin was also present in glial cells and in the olfactory bulb, sub-ventricular zone and dentate gyrus, areas where neurogenesis and synaptic plasticity are maintained throughout adult life. The hepcidin species identified by Western blotting in sub-ventricular zone, cortex and hippocampus migrated as a ~2.8 kDa band, identical in size to hepcidin present in normal rat serum suggesting that hepcidin in brain was the full-length biologically active 25 amino acid peptide. Hepcidin co-localised with ferroportin in ependymal cells of the sub-ventricular zone and in the corpus callosum consistent with a regulatory role in iron metabolism at these sites. CONCLUSIONS: Hepcidin protein was widely expressed in brain parenchyma while levels of hepcidin gene transcription appeared to be below the limits of detection of the in situ hybridisation probes. This disparity suggests that not all hepcidin in the brain is transcribed in situ and may originate in part outside the brain. The properties of hepcidin as a cationic peptide hormone are reflected in the finding of hepcidin in the walls of blood vessels and in pericytes and glia, cells that may be involved in transporting the peptide into brain interstitium.
Keywords: fluorescenční protilátková technika; neuroglie; mozek; Humans; messenger RNA; lidé středního věku; In Situ Hybridization; dítě; hybridizace in situ; Child; Blood Chemical Analysis; pericyty; Neuroglia; Aged; mladý dospělý; dospělí; hepcidiny; senioři; lidé; zvířata; Hepcidins; Adult; RNA, Messenger; potkani Sprague-Dawley; Endothelial Cells; Middle Aged; Brain; Adolescent; endoteliální buňky; Real-Time Polymerase Chain Reaction; Young Adult; biochemická analýza krve; Fluorescent Antibody Technique; Rats, Sprague-Dawley; Animals; Pericytes; kvantitativní polymerázová řetězová reakce; mladiství